Effect of obstructive sleep apnea on hypertension - S A Akkara; D A Shah; A G Akkarra; A A Singhania (Journal of Integrated Health Sciences)
Aim: To find out using the Berlin questionnaire the presence of high risk of Obstructive Sleep Apnea Syndrome (OSAS) in patients of hypertension and to find its relation with severity of hypertension. Methods: All patients of essential hypertension undergoing treatment in our institute were included in the study. All patients filled up the Berlin questionnaire. The questionnaire was scored for positivity and the data was analysed for rate of positivity and relationship with severity of hypertension. Results and discussion: 964 patients were included in the study. Majority of the patients were male and mostly in the sixth decade of life. 522 cases were positive for high risk of OSAS in terms of Berlin questionnaire. Analysis of data showed the proportion of males was more, the patients were older and BMI was more among the Berlin positive cases as compared to Berlin negative cases. Analysis also revealed that Berlin positivity rate was higher in patients with higher severity of hypertension as deemed by the use of more than one anti hypertensive drug as compared to hypertensive patients using only one anti hypertensive drug. These results reaffirm the significant association of OSA with the development and increase in severity of hypertension as reported in contemporary literature. Conclusion: Greater proportion of patients with severe hypertension had OSA than those with mild or no hypertension. Hence it should be investigated in the general work up of hypertensive patients.